AKUNTANSI SYARIAH PERUSAHAAN DAGANG (MURABAHAH) - Latifah, Eny; Abdullah, Rudi; Adnan Hakim, Al Asy Ari (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2022)
The purpose of this study was to determine the concept of accounting in trading companies with murabahah approach. The research method used is qualitative with the type of literature study. The results showed that merchandising businesses is an organization that uses its resources to provide products obtained from other parties for its customers. Islamic accounting of trading companies often uses murabahah, salam and istishna contracts. Cost of goods in Islamic accounting of trading companies is mentioned with a description of the amount of cash or cash equivalents paid to acquire an asset until the asset is in a place and condition ready for use/sale in accordance with (PSAK 102). Islamic accounting treatment in trading companies includes: accounting for sellers and buyers, recognition of asset acquisition and profit, treatment of discounts or rebates and others